Heterogeneity of marine birnaviruses isolated from turbot (Scophthalmus maximus) - Novoa, Beatriz; Figueras Huerta, Antonio (Japanese Society of Fish Pathology, 1996)
6 pages, 1 figure, 1 table Six marine birnaviruses isolated from turbot (Scophthalmus maximus) were compared with the infectious pancreatic necrosis virus reference strains Sp, Ab and WB from salmonid fish. This comparison was carried out by PAGE analysis of viral RNA and polypeptides and comparison of the reaction pattern with 4 monoclonal antibodies against the reference strains. High heterogeneity was found among the 6 isolates when comparing the RNA and polypeptide electrophoretic patterns and their reactions with the monoclonal antibodies. Most of the strains isolated from turbot could not be ascribed to any established serotype Beatriz Novoa acknowledges the Ministerio de Educacion y Ciencia (Spain), for research fellowship. This work was supported by Grant AGF93-0769-C02-02 of the Comision Interministerial de Ciencia y Tecnologia (CICYT) Peer reviewed